MASTER of the Game : Henry Kissinger and the Art of Middle East Diplomacy - Indyk, Martin (New York : Alfred A. Knopf, 2021)
"A perceptive and provocative history of Henry Kissinger's diplomatic negotiations in the Middle East that illuminates the unique challenges and barriers Kissinger and his successors have faced in their attempts to broker peace between Israel and its Arab neighbors"-- Provided by publisher.
Includes index
Keywords: Kissinger, Henry, -- 1923-; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Middle East; Foreign relations -- 1969-1974; United States -- Foreign relations -- 1974-1977